Scientific data for CS-MAP in Cambodia - Bui Tan Yen (International Rice Research Institute, 2022)
The presentation elaborated on the various scientific data used to develop Climate-Smart Mapping and Adaptation Planning (CS-MAP) for Cambodia. These include spatial data for flood risk and drought risk, land cover/land use type, and other spatial data (i.e., administrative boundary, natural resources, satellite images, and topography).